Lethal action of ovarian hyper excess luteinization and progesterone on embryos and fetuses - San Martín, M. (1954)
Excess progesterone and luteinizing ovarian hyper apparently produce embryonic death, not only in pregnancies that are concomitantly begin to endogenous or exogenous excess progesterone, but also in pregnancies that existed before hormone produced surcharge.